2021
DOI: 10.1136/bmjopen-2020-045870
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and its association with adults’ mental health problems: a cross-sectional study among men and women in the Yangon Region of Myanmar

Abstract: ObjectivesTo estimate the prevalence of emotional, physical and sexual childhood abuse, and symptoms of post-traumatic stress disorder (PTSD) and to examine the association between childhood abuse and adult mental health problems, including mental distress and PTSD symptoms.DesignA community-based cross-sectional study was conducted. Childhood abuse was assessed with the NorVold Abuse Questionnaire, and mental distress and symptoms of PTSD were measured using the Hopkins Symptom Checklist 10 and the Impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…As many as 120 million women under the age of 20 experience forced sexual contact (WHO, 2022). This statement is in line with research conducted by Aye et al, (2021) in Myanmar on 2,377 adults aged 18-49 years who stated that the prevalence of women with experiences of sexual violence in childhood was higher than that of men ( 13.3% vs. 1.3%). A quarter of the study population had experienced a traumatic event in which 26% reported experiencing PTSD.…”
Section: Sexual Violence In Childhood Withsupporting
confidence: 90%
“…As many as 120 million women under the age of 20 experience forced sexual contact (WHO, 2022). This statement is in line with research conducted by Aye et al, (2021) in Myanmar on 2,377 adults aged 18-49 years who stated that the prevalence of women with experiences of sexual violence in childhood was higher than that of men ( 13.3% vs. 1.3%). A quarter of the study population had experienced a traumatic event in which 26% reported experiencing PTSD.…”
Section: Sexual Violence In Childhood Withsupporting
confidence: 90%
“…One study indicated that children in rural areas encountered elevated levels of corporal punishment in schools [50], which was supported in another study in Mali and Libya [77]. Risk factors associated with child abuse and maltreatment, including gender, older age, rural residence, family socioeconomic status, family size, parent's education, and parent's alcohol use, were similar to those reported in a study in Saudi Arabia [78] and to findings from conflict-affected countries, including Pakistan [79] and Myanmar [80].…”
Section: Violence Against Childrensupporting
confidence: 76%
“…The present manuscript reports an analysis of data from a population-based, cross-sectional study among men and women aged 18-49 years in the northern and southern districts of the Yangon Region of Myanmar, conducted in October and November 2016. [52][53][54] Data were collected in the Yangon Region, the most developed and densely populated region in Myanmar, and included all ethnic groups residing there. However, it excluded nuns, monks, soldiers, institutionalised people and those deemed too ill physically and/or mentally to participate.…”
Section: Study Design and Settingmentioning
confidence: 99%